Flexible feeding kinematics of a tropical carnivorous anuran tadpole - Sousa, V. T. T. de; Nomura, F.; Venesky, M. D.; Rossa-Feres, D. C. [UNESP]; Pezzuti, T. L.; Andrade, G. V.; Wassersug, R. J. (Wiley-Blackwell, 2014)
Leptodactylus labyrinthicus tadpoles are known predators of anuran eggs and hatchlings, but they are also able to filter-feed in the water column and scrape food off of firm substrates. We evaluated and compared these alternative feeding behaviors in relation to feeding kinematics and the shape of the mouth with high-speed digital imaging. We tested the hypotheses that (1) L.labyrinthicus tadpoles use functionally different feeding kinematics when feeding on alternative food sources and (2) that the jaw sheaths of L.labyrinthicus tadpoles deform less during filter-feeding and substrate grazing compared with more common tadpoles not so specialized for macrophagous carnivory. Our results show that filtering and scraping feeding behaviors differ significantly in both kinematics and shape of the mouth. During filter-feeding, tadpoles display longer gape cycles and attain a narrower maximum gape earlier in the cycle compared with substrate grazing. Jaw deformation during opening and closing phases of the gape cycle is more pronounced during grazing on firm substrates. This deformation contributes to the achievement of a wider maximum gape during feeding. These differences appear to reflect behavioral adjustments by the tadpoles to maximize food intake. Feeding in tadpoles of L.labyrinthicus is not restrained by their typical carnivorous morphology. On the contrary, L.labyrinthicus tadpoles seem to be opportunistic feeders able to obtain nutrients from a variety of food sources by using different feeding strategies.
Keywords: Anura; behavioral plasticity; biomechanics; geometric morphometrics; food source